Measuring the integration of primary care and behavioral health services. (6th February 2019) - Mullin, Daniel J.; Hargreaves, Lee; Auxier, Andrea; Brennhofer, Stephanie A.; Hitt, Juvena R.; Kessler, Rodger S.; Littenberg, Benjamin; Macchi, C. R.; Martin, Matthew; Rose, Gail; Trembath, Felicia; van Eeghen, Constance
Abstract : Objective: To perform a factor analysis of the Practice Integration Profile (PIP), a 30‐item practice‐level measure of primary care and behavioral health integration derived from the Agency for Healthcare Research and Quality's Lexicon for Behavioral Health and Primary Care Integration. Data Sources: The PIP was completed by 735 individuals, representing 357 practices across the United States. Study Design: The study design was a cross‐sectional survey. An exploratory factor analysis and assessment of internal consistency reliability via Cronbach's alpha were performed. Data Collection Methods: Participant responses were collected using REDCap, a secure, web‐based data capture tool. Principal Findings: Five of the PIP's six domains had factor loadings for most items related to each factor representing the PIP of 0.50 or greater. However, one factor had items from two PIP domains that had loadings >0.50. A five‐factor model with redistributed items resulted in improved factor loadings for all domains along with greater internal consistency reliability (>0.80). Conclusions: Five of the PIP's six domains demonstrated excellent internal consistency for measures of health care resources. Although minor improvements to strengthen the PIP are possible, it is a valid and reliable measure of the integration of primary care and behavioral health.